(untitled) (Semiárida, 2019)
Rangelands can be managed ecologically so that they remain productive and environmentally stable. Cattle movement in pastures is directly related to the size of the paddock and the water source location. Grazing, even with moderate stocking rates, produce important floristic gradient with a reduction in the number of forage species nearby to the water source areas. The seed bank plays an important role in population plant maintenance and pasture recovery after a disturbance. The aim of this study was to evaluate how grazing time and distance to the water supply (near, middle and far), affects some population parameters of Piptochaetium napostaense and seed bank. The longer the grazing time, the more affected the population parameters (crown diameter, number of stems and seeds per plant) are, as well as the number of propagules in the bank. Extended grazing times in areas near the water source will benefit the seed bank of nonforage warm season rhizomatous species.